COMPARATIVE ANALYSIS OF DISABILITY RIGHTS: NATIONAL AND INTERNATIONAL LEGAL FRAMEWORKS (International Journal of Food and Nutritional Sciences, 2022)
This study examines the alignment and divergence between national disability rights frameworks and international standards, particularly the United Nations Convention on the Rights of Persons with Disabilities (CRPD). By analyzing legal frameworks in selected countries, such as the United States and India, alongside international instruments, this research highlights both advancements and gaps in the protection of disability rights. Findings reveal that while many national laws adopt core CRPD principles, significant disparities persist, particularly in enforcement mechanisms and accessibility standards. For instance, the Americans with Disabilities Act (ADA) emphasizes anti-discrimination and accessibility but relies heavily on individual complaints, which limits its systemic impact. Meanwhile, India's Rights of Persons with Disabilities Act (RPWD) reflects CRPD ideals but faces resource and infrastructure limitations, especially in rural areas. The study underscores the influence of cultural and socioeconomic factors on the implementation of disability rights, suggesting that future policy development should prioritize adaptable, context-specific strategies to enhance compliance and inclusivity. This comparative approach contributes to the global discourse on disability rights, providing recommendations for harmonizing national policies with international standards to promote equal rights for persons with disabilities worldwide.